Replacing plastic bread clips with cardboard will prevent bowel perforation. Issue 12 (25th June 2022) - Andersen, Lalita Maria; Yuide, Peter
Abstract: Plastic bread clips cause significant morbidity and mortality if accidentally ingested. A review of all existing case reports published in medical literature was conducted in PubMed, MedLine and Google Scholar. Key words included but was not limited to; clip, tag, tab, closure, kwik lok, bread, bag, ingestion, bowel, obstruction, perforation, plastic and foreign body. References of all the articles were sought out to ensure completeness. Fifty‐six cases between 1975 and 2020 were analysed to understand the complications and the characteristics of the bread clip that caused these. About 28% of case reports described bowel perforation, with 61% of these occurring in the small bowel. Plastic bread clips are firm in nature, long lasting, and are shaped to grasp onto bowel, thus leading to these complications. Commercially available alternatives are introduced in order to encourage replacing plastic bread clips worldwide. Abstract : Plastic bread clips have been causing bowel perforation since its invention. In the past 12 months, Australia has finally presented an alternative that should prevent further perforations. The aim of this article is to encourage other countries to follow suit, in order to protect the demographics at risk.